Acoustic and Flow Aspects of Novel Synthetic Jet Actuator - Emil Smyk; Paweł Gil; Rafał Gałek; Łukasz Przeszłowski (Actuators, 2020)
The acoustic and flow aspects of the novel synthetic jet actuator (SJA) with fins inside the cavity were experimentally investigated for three types of enclosure design and two models of loudspeaker. The aim of the study is to find the parameter which connects the flow and acoustic properties of the SJA and allows us to choose the optimal solution in those regards. The hot wire anemometry was used for the velocity measurements and the sound pressure level was measured with a sound level meter. The model of the loudspeaker turned out to have a significantly stronger impact on the flow parameters and noise level than the shape of the fins in the cavity. The parameter that showed a dependence on the shape of the fins was the actuator’s efficiency. A ratio of the root-mean-square velocity at the orifice axis to the sound pressure level (U0.c/SPL) was used to connect the acoustic and flow properties of the tested actuators. This parameter was subsequently applied to determine the best configuration among the tested actuators.